Nadzieja na wieczność według Chantal Delsol - Przybylska, Nelli (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
Monique Atlan and Roger-Pol Droit both propose a reassessment of the dominant rationalistic pessimism of people through the perspective of hope. From this point of view, one should definitely learn thinking also in terms of hope. According toChantal Delsol, European pessimism can be overcome with Christian faith. The hope of eternal life derives from the Jewish and Christian principles of faith. The respect for eternityoriginated the great achievements of civilization. The philosopher attempts to transpose this spiritual program and values onto a social plan.Similar perception of hope in the perspective of faith coincides, despite the distinctarticulation, in the Peguy’s poem. For Peguy the figure of a little girl personifies the frailand weak hope. According to Delsol, the European hope can be rebuilt through the anthropologicalvision of a fragile man. Her concept of hope is based on the acceptance ofhuman imperfection.